2000
DOI: 10.1016/s0886-3350(00)00309-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mitomycin-C on posterior capsule opacification in rabbit eyes

Abstract: Our results suggest that the application of mitomycin-C dissolved in sodium hyaluronate effectively reduces PCO in rabbit eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Antiproliferative treatments have been applied to LECs in different conditions such as in vitro cell culture, in vivo (including rabbits, monkeys, and humans), and in vitro capsular bag models. 8,16,19,[20][21][22][23] The drugs were delivered to LECs by different carriers such as OVDs, BSS, and controlled release implants or added directly to growth media in cell culture in vitro experiments. 20,24 As in Nishi's study, 11 at the end of the follow-up, there was no significant difference relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Antiproliferative treatments have been applied to LECs in different conditions such as in vitro cell culture, in vivo (including rabbits, monkeys, and humans), and in vitro capsular bag models. 8,16,19,[20][21][22][23] The drugs were delivered to LECs by different carriers such as OVDs, BSS, and controlled release implants or added directly to growth media in cell culture in vitro experiments. 20,24 As in Nishi's study, 11 at the end of the follow-up, there was no significant difference relative to the control.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the obstruction rates of visible light are expressed as an index of PCO by a modification of the method of Chung et al [9]. In the previous method, we thought that the magnifying effects of the retained intraocular lens might alter the obstruction rate values, Kruskal Wallis test with multiple comparisons (Tukey method).…”
Section: Discussionmentioning
confidence: 92%
“…To evaluate the degree of PCO quantitatively, the obstruction rate of visible light, we used the method of Chung et al [9]. The intraocular lenses were carefully removed after enlarging the anterior capsular opening, and the retracted anterior capsules were trimmed.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature has shown significant benefits as well as considerable adverse outcomes, ranging from conjunctival thinning to corneal/scleral melt at typical concentrations of 0.04% and above for MMC-enhanced trabeculectomies. Complications ranging from corneal dellen [1], corneal endothelial toxicity [2], and chronic conjunctival leakage [3] to endophthalmitis [4] following trabeculectomy have been reported. Muckley and Lehrer [5] reported on the incidence of late-onset blebitis/endophthalmitis with MMC.…”
Section: Discussionmentioning
confidence: 99%